2020
DOI: 10.1111/jvh.13281
|View full text |Cite
|
Sign up to set email alerts
|

Chronic hepatitis C treatment in HIV co‐infection in Portugal: Results from a cohort OF 2133 patients presented by GEPCOI (Portuguese Coinfection Study Group)

Abstract: Direct‐acting antiviral drugs (DAAs) have recently changed the paradigm of hepatitis C therapy, significantly improving treatment response rates, patient life expectancy and quality of life. In Portugal, sofosbuvir (SOF) and SOF/ledipasvir (SOF/LDV) were fully reimbursed by the National Health System since early 2015 and generalized use of interferon‐free DAA based regimens became current practice. During 2016, the remaining DAAs were sequentially added and covered by the same health access policy. The Portugu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
(15 reference statements)
1
0
3
Order By: Relevance
“…Several previously reported studies have shown the same response. 19 , 20 , 21 , 22 , 23 In contrast to our findings, Gayam et al . reported lower rate of SVR in HIV/HCV co‐infection group (84% vs 94%).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Several previously reported studies have shown the same response. 19 , 20 , 21 , 22 , 23 In contrast to our findings, Gayam et al . reported lower rate of SVR in HIV/HCV co‐infection group (84% vs 94%).…”
Section: Discussioncontrasting
confidence: 99%
“…Several previously reported studies have shown the same response. [19][20][21][22][23] In contrast to our findings, Gayam et al reported lower rate of SVR in HIV/HCV co-infection group (84% vs 94%). 24 In this study, the majority of patients was no/mild liver fibrosis by APRI score (68%) and GT1 was predominant genotype (66%), as well as the HIV status was good regarding high CD4 count and low HIV viral load, which may explain the high SVR rate.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…SVR12 for patients using SOF-DCV regimen was achieved by 176 of 184 patients (95.7%). This SVR rate was comparable with rates reported in phase III studies [ 28 ], and other real-life situations in HIV/HCV co-infection [ 15 , 16 , 29 , 30 ], even though HCV genotyping was not a requirement of starting this treatment program. A recent meta-analysis has shown that the SVR12 rate of SOF-DCV±RBV among HIV/HCV co-infected patients in clinical-trials was 97% (95% CI 93–99%), and in real-world studies 94.1% (95% CI 91.2–96.4%) [ 4 ].…”
Section: Resultssupporting
confidence: 85%